TWO HATS OR ONE: THE CO-DEPENDENT WORLDS OF JONATHAN HARVEY'S CHURCH AND CONCERT MUSIC. (January 2023) - Hughes, Ed
Abstract: This article scrutinises the composer Jonathan Harvey's remark that 'most of my colleagues see me as wearing two hats: one a church music composer's, the other an avant-garde instrumental/electronic composer's. I wish I could say it was one hat. I think of all my music as sacred in a sense.' The article considers Harvey's church and concert works as linked worlds in order to propose a more holistic appreciation of his stylistic and technical innovations and that, far from being occasional pieces, his music for the church played an active role in the development of the composer's language, in part because singing was a formative experience for Harvey, and in part because collaborative work with choirs, church musicians and associated artists and thinkers was so frequently fertile. Based on the composer's own notes to the author, the article concludes with an account of the composition process involved in the creation of Plainsongs for Peace and Light (2012), a work for unaccompanied mixed choir or 16 solo voices, which the composer described as 'elaborations' of chant.